2009
DOI: 10.3732/ajb.0800035
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of an endangered Utah endemic, Astragalus ampullarioides (Fabaceae)

Abstract: The endangered Shivwits milkvetch, Astragalus ampullarioides, is a perennial, herbaceous plant. This Utah endemic was federally listed as endangered in 2001 because of its high habitat specificity and low numbers of individuals and populations. All habitat currently occupied by A. ampullarioides was designated as critical by the U.S. Fish and Wildlife Service in 2006 as a result of conservation litigation. We used AFLP markers to assess genetic differentiation among the seven extant populations and quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…A study by Hoeck et al (2010) showed that the degree of population divergence through drift strongly depends on habitat size which correlated with N e . Heath et al, 2002;Morris, Baucom & Cruzan, 2002;Breinholt et al, 2009;Griffith et al, 2009). Similarly strong genetic drift was shown by Harper et al (2006) for a butterfly species.…”
Section: Effective Population Size and Random Genetic Driftmentioning
confidence: 59%
“…A study by Hoeck et al (2010) showed that the degree of population divergence through drift strongly depends on habitat size which correlated with N e . Heath et al, 2002;Morris, Baucom & Cruzan, 2002;Breinholt et al, 2009;Griffith et al, 2009). Similarly strong genetic drift was shown by Harper et al (2006) for a butterfly species.…”
Section: Effective Population Size and Random Genetic Driftmentioning
confidence: 59%
“…There are still relatively few Malagasy species for which population genetic information is available, so our investigation of Delonix provides a useful starting point for comparison with other regions around the world. Compared to results for other AFLP studies on species of conservation concern, the Shannon's Index for our Madagascar-based investigation of Delonix Tests of significance were based on 999 permutations (0.076-0.192) show similar levels to other species of conservation concern (for example Baskauf and Burke 2009;Breinholt et al 2009;Cardoso et al 2005;Juan et al 2004;Rivera-Ocasio et al 2006;Song et al 2008 Cardoso et al 2005). Despite being one of the world's most species-rich biodiversity hotspots (Brummitt and Nic Lughadha 2003;Mittermeier et al 2005;Myers et al 2000), the information on genetic variation for Malagasy plants is sparse, and this study more than doubles the knowledge base of Madagascar's plant genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Use of dominant marker data in genetic diversity analysis can lead to estimation bias with overestimating parameters by as much as 5%, especially with small sample sizes [25][26]. To account for this potential bias, Lynch and Milligan proposed pruning any locus with a band frequency of higher than 1-(3/N), where N is the number of individual samples [25].…”
Section: Methodsmentioning
confidence: 99%